Avian Antimicrobial Host Defense Peptides: From Biology to Therapeutic Applications - Guolong Zhang; Lakshmi T. Sunkara (MDPI AG, 2014)
Host defense peptides (HDPs) are an important first line of defense with antimicrobial and immunomoduatory properties. Because they act on the microbial membranes or host immune cells, HDPs pose a low risk of triggering microbial resistance and therefore, are being actively investigated as a novel class of antimicrobials and vaccine adjuvants. Cathelicidins and β-defensins are two major families of HDPs in avian species. More than a dozen HDPs exist in birds, with the genes in each HDP family clustered in a single chromosomal segment, apparently as a result of gene duplication and diversification. In contrast to their mammalian counterparts that adopt various spatial conformations, mature avian cathelicidins are mostly α-helical. Avian β-defensins, on the other hand, adopt triple-stranded β-sheet structures similar to their mammalian relatives. Besides classical β-defensins, a group of avian-specific β-defensin-related peptides, namely ovodefensins, exist with a different six-cysteine motif. Like their mammalian counterparts, avian cathelicidins and defensins are derived from either myeloid or epithelial origin expressed in a majority of tissues with broad-spectrum antibacterial and immune regulatory activities. Structure-function relationship studies with several avian HDPs have led to identification of the peptide analogs with potential for use as antimicrobials and vaccine adjuvants. Dietary modulation of endogenous HDP synthesis has also emerged as a promising alternative approach to disease control and prevention in chickens.